The child reader, 1700-1840 - Grenby, M O. (Cambridge University Press, 2011)
"Children's literature, as we know it today, first came into existence in Britain in the eighteenth century. This is the first major study to consider who the first users of this new product were, which titles they owned, how they acquired and used their books, and what they thought of them. Evidence of these things is scarce. But by drawing on a diverse array of sources, including inscriptions and marginalia, letters and diaries, inventories and parish records, and portraits and pedagogical treatises, and by pioneering exciting new methodologies, it has been possible to reconstruct both sociological profiles of consumers and the often touching experiences of individual children. Grenby's discoveries about the owners of children's books, and their use, abuse and perception of this new product, will be key to understanding how children's literature was able to become established as a distinct and flourishing element of print culture"--